ANALYSIS OF THE APPLICATION OF THE ART OF WAR PRINCIPLES TO BUSINESS STRATEGY: A LITERATURE-BASED CASE STUDY OF AMAZON - Sabitah, Nur Azizah (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Jeff Bezos has successfully developed Amazon into one of the world’s largest e-commerce and technology companies. This success has been influenced by the business strategies it has implemented. The Art of War, written by Sun Tzu, is one of the military strategy texts that continues to be widely discussed. Sun Tzu explains various principles that must be applied to achieve victory. These principles are also relevant in a business context. This article explains Amazon’s business strategy by using a military strategic perspective, namely The Art of War. This article employs a qualitative approach based on secondary data. The analysis process was conducted by mapping the principles of The Art of War onto Amazon’s strategies, which were derived from Amazon’s official publications and academic literature. The literature analysis shows that Amazon’s business strategy applies several principles of The Art of War, namely terrain and ground, flexibility, maneuvering, opportunism, fiery attack, and energy direct position. This article produces a new analytical framework that maps the six principles of The Art of War onto three of Amazon’s business strategies, namely product innovation through diversification, supply chain management, and distribution. The application of these principles has helped Amazon adapt quickly to change, achieve competitive advantage, and generate profit.